Relation of left atrial overload indices with prognostic endpoints in heart failure and preserved ejection fraction. (2nd March 2022) - Hoshida, Shiro; Tachibana, Koichi; Shinoda, Yukinori; Minamisaka, Tomoko; Seo, Masahiro; Yano, Masamichi; Hayashi, Takaharu; Nakagawa, Akito; Nakagawa, Yusuke; Tamaki, Shunsuke; Yamada, Takahisa; Yasumura, Yoshio; et al.
Abstract: Aims: Considerable variation in the relationships between the indices of left atrial (LA) volume and pressure could possibly affect the selection of medications or efforts to improve the prognoses of patients with heart failure and preserved ejection fraction (HFpEF). We aimed to clarify the association between the prognostic endpoint and LA overload indices in elderly patients with HFpEF. Methods and results: We analysed 898 patients with HFpEF hospitalized for acute decompensated heart failure (men/women: 406/492). Blood tests and transthoracic echocardiography were performed before discharge. The primary endpoint was re‐admission for heart failure or all‐cause mortality. Stroke volume (SV)/left atrial volume (LAV), an index for LA volume overload, was a significant prognostic factor of re‐admission for heart failure in the multivariable Cox hazard analysis adjusted for comorbidities [hazard ratio (HR) 0.616, 95% confidence interval (CI) 0.430–0.882, P = 0.008]. Additionally, the ratio of diastolic elastance (Ed) to arterial elastance (Ea), an index for LA pressure overload, was also significant (HR 1.444, 95% CI 1.014–2.058, P = 0.041). Furthermore, Ed/Ea, but not SV/LAV, was a significant prognostic factor of all‐cause mortality (HR 1.594, 95% CI 1.102–2.306, P = 0.013). Conclusions: The index of LA overload for prognosis may differ according to the different endpoints in elderly patients with HFpEF.